The Role of Career Exploration Behavior as A Mediator in The Relationship Between Social Support and Career Decision Self-Efficacy Among High School Students - Barusi, Atika Rahmania El; Suharso, Puji Lestari (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to analyze the role of career exploration behavior as a mediator of the relationship between social support and career decision self-efficacy (CDSE) among high school students. This study used a cross-sectional study design with a quantitative approach. The participants were in 10th and 11th grade in Jabodetabek High Schools (N = 130). Data were collected using convenience sampling. The instruments used in this research comprised the Career Decision Self-Efficacy-Short Form (CDSE-SF), Adolescent Social Support Scales (ASSS), and Career Exploration Survey (CES). All data were analyzed statistically by descriptive, correlation, and mediation analysis. The results show that career exploration behavior fully mediates the relationship between social support and CDMSE (c = 0.208; p < 0.001). While external support from parents, teachers, and friends is crucial, internal factors are equally essential to help high school students plan their careers effectively. High school students need access to various useful information from their surroundings to actively engage in career exploration and gain the confidence needed to make informed career decisions. In this study, it was found that for students to have career decision self-efficacy, social support and career exploration behavior are needed in high school students.